Value-Chain in Beach Tourism: The Consideration of Maslahah in Strategic Formulation - Thaha, Fathurrahman; Parakkasi, Idris; Sirajuddin, Sirajuddin; Fathurrahman, Rezki Amalia (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
This study aims to analyze the activities on tourism beaches using the value chain and maslahah analysis. This research is a phenomenological qualitative study with a purposively-selected sampling of stakeholders in Dato Beach, Majene, Indonesia. This study found that the immediate strategy highlights in the form of beautiful natural panoramas must be prioritized and marketed. This study reports that the chains must present the flow of operations, exit logistics visitors, promotions, adequate facilities and infrastructures, and affordable tickets. Halal tourism destination brings benefit image to customer perceptions.